FEATURES OF THE TRANSFORMATION OF NATURAL GAS TRANSPORTATION AND DISTRIBUTION ENTERPRISES IN THE CONDITIONS OF THE ENERGY TRANSITION - Дзьоба, Олег Григорович; Гараздюк, Володимир Васильович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article researches theoretical and methodological approaches focused on the development and substantiation of conceptual decisions regarding the formation of adaptation potential and the determination of individual transformation trajectories of gas transportation and gas distribution enterprises in the medium and long term in the conditions of the implementation of the energy transition. The prerequisites and features of the energy transition at the current stage of human development are characterized. It has been proven that in the process of energy transition, national governments, business structures and individual business entities, research organizations will have to solve a number of complex tasks related to the need to transform the existing infrastructure of production, extraction, processing, transportation, distribution, storage and consumption fossil fuels. It has been established that such tasks will cover almost all production sectors of national economies, and will also concern households, that is, the communal and household sphere. The conditions and features of the technical, technological, production, economic, organizational and managerial reformation of pipeline transport and natural gas distribution enterprises in connection with global tasks related to the implementation of the energy transition have been studied. In the process of research, the key features of the formation and development of the gas transportation system of Ukraine were analyzed, the change in its role on the domestic and European gas markets in the second and third decades of the 21st century was characterized, the necessity of solving a number of strategic tasks regarding the reform of its production capacities, technical and technological, resource and adaptation was proved potential, as well as the specifics of the transformation of natural gas transportation and distribution enterprises are defined, and the conceptual foundations of the strategy formation of such transformational changes are outlined.